Turbulent Velocity Fluctuations as Affected by Biotic and Abiotic Windbreaks under Field Conditions - Amiri, Iraj; Taei, Javad; Ekhtesasi, Mohammad Reza; Shahryari, Ali Reza (Global Journal of Food and Agribusiness Management, 2022)
Windbreaks have been used for centuries to shelter crops from wind damage and to protect soils from wind erosion. This study was performed in 5 steps to evaluate the effects of biotic and abiotic windbreaks on mean horizontal flow and turbulent velocity fluctuations under field conditions. These steps included of granolometery analyzing, determination of field threshold velocity of soil erosion, estimation of acceptable wind speed, optimizing windbreak distance and wind speed recording. Two kinds of windbreaks were used in this study, include of biotic windbreak (Tamarix aphylla) with 45% density and abiotic windbreak (Mud wall) with 100% density. Results of field experiment showed that optimized distances for abiotic and biotic windbreak are respectively observed at 7.87h and 4.5h after windbreak. Finally mud wall is applicable for high decreasing wind speed at the back of windbreak but its high wind speed fluctuation and high turbulent were limited these windbreak in agro ecosystem. Tamarix aphylla with 45% density is applicable for medium decreasing of wind speed and creating low turbulent after windbreak.